Ecologia populacional do amblipígeo Charinus eleonorae Baptista & Giupponi 2003 (Arachnida: Amblypygi: Charinidae) e dos opiliões Iandumoema uai Pinto-da-Rocha 1996, Eusarcus cavernicola Hara & Pinto-da-Rocha 2010 e Eusarcus aduncus Mello- Leitão 1942 (Arachnida: Opiliones: Gonyleptidae) da Gruta Olhos d’ Água, Itacarambi, Minas Gerais - Monte, Bruno Gabriel Oliveira do (Universidade Federal de São Carlos, 2017)
In Brazil several works were carried out considering a general diversity of underground organisms from different regions. The Parque Nacional Cavernas do Peruaçu (PNCP), near the municipality of Itacarambi, Minas Gerais states, highlighted by works carried out with the troglobite catfish (exclusive of subterranean environment) Trichomycterus itacarambiensis Trajano and Pinna (1996), the end of the Olhos d’ Água cave. In addition to catfish, a cave is home to other populations of troglobites, such as the harvestmen Iandumoema uai Pinto-da-Rocha (1996) and the whip spider Charinus eleonorae Baptista and Giupponi (2003). The populations of the Eusarcus cavernicola Hara and Pinto-da-Rocha (2008) and Eusarcus aduncus Mello-Leitão (1942). Considering the populations of the mentioned arachnid species, we investigated from the marking and recapture method as size and population density. In addition, we analyzed the distribution of the troglóbios (I. uai and C. eleonorae) in relation to troglófilos (E. cavernicola and E. aduncus). Finally, from collections made in caves of the PNCP analyzes a diversity of the subterranean fauna in relation to Olhos d 'Água cave. Our results showed that the population of I. uai opium is numerically higher than others, with population values and higher densities. In addition, I. uai widely distributed in the various regions of the Olhos d 'Água cave, as well as C. eleonorae. In contrast, E. cavernicola and E. aduncus are restricted within the cavern with populations secreted relative to I. uai and C. eleonorae. Still, the Olhos d 'Água cave presents greater subterranean diversity with occurrence of troglophiles, troglóbites and relict specie.
Keywords: Peruaçu; Estimativa populacional; Diversidade subterrânea; Population estimate; Subterranean diversity; CIENCIAS BIOLOGICAS::ECOLOGIA